Analysis of the IHF binding site in the regulatory region of bacteriophage Mu. - van Rijn, P A (1991)
In bacteriophage Mu the converging early and repressor transcriptions are both stimulated by binding of IHF to the same region, which is located just upstream of the early promoter (Pe) and 100 base pairs downstream of the repressor promoter (Pc). Within this region two sequences are present (ihfa and ihfb) that match the consensus sequence for IHF binding. These sequences are partially overlapping and in inverted orientation. In this paper we describe the effect of mutations in the non-overlapping part of ihfa and ihfb on the binding of IHF. We show that IHF has a very strong preference to bind to ihfb even when a mutated ihfa has a better match with the consensus. A stretch of A residues located nine base pairs from the ihfb sequence appears to play an important role in the stability of the DNA-IHF complex, but not in the discrimination between the two putative binding sites. In addition we describe the effect of the mutations on the stimulation of early and repressor transcription. We show that for activation of the Pc promoter a stable complex between IHF and the DNA is required, whereas for normal Pe stimulation a much weaker DNA-IHF interaction is sufficient.